ISLAMIC PERSPECTIVE OF THE ENVIRONMENT IN LINE WITH ENVIRONMENT-CENTERED AND HUMAN-CENTERED APPROACHES - Faruk ÖZDEMİR (Fırat University, 2019)
Today, people are confronted with environmental problems that threaten the existence of both humanity and other living creatures. These problems have reached unprecedented levels and affect industrial zones, oceans, all the continents and even affect the mechanisms of the global order. Environment-centered and human-centered approaches are encountered in general for the solutions proposed to solve these environmental problems and deal with environmental issues. Religions, especially Abrahamic religions have been criticized in terms of this human-centered approach. Lynn White criticizes the Christian-Jewish tradition claiming that everything is created for humanity in particular. Arnold Toynbee is not limiting this claim with only the tradition of Christian-Jewish and therefore including Islam in this issue by suggesting that all monotheistic religions have a part in the emergence of this problem. This article will examine the issue in view of Islam. In this regard, it will be emphasized that Islam offers neither environment-centered nor people-centered approaches only. In Islam, there are many verses highlighted in regard with “dimension” and “teleology” of the environment for humanity. Furthermore, the dimension of “sanctity” indicating the value, effect and importance of environment is also emphasized. Thus, since the relationship between human and environment cannot be explained by only two dimensions as environment-centered or human-centered approaches, this irreducibility will be discussed within the scope of “trust” in Islam. In other words, Islam degrades the relationship between humanity and environment to the level of neither environment-centered nor human-centered approaches. From this point of view, it is clear to see that people are being tested in the world with the responsibility of being entrusted and caliphates in their relations with the environment. In other words, considering the approach of Islam, we are advised to be on the mid-way point as ummah against environment-centered and human-centered approaches. In this context, the responsibility is realizing that people have the right to utilize natural resources, but also have to protect them as well. This is a moral and ethical call. In this context, it will be discussed that Islam is offering an understanding and experience that ensure formation of a critical awareness for taking part in both extreme attitudes.